Angkutan Sedimen Menggunakan Metode Yang Pada Sungai Sombe, Palu, Sulawesi Tengah - Pratama, M.I. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
The sedimentation process that occurs in in Sombe River is a phenomenon of sediment grainsor particles entrained from the riverbank avalanche. The problem is exacerbated when there is moderate to high intensity rainfall, causing sediment material transported by a flood. The purpose of this study is to identify and estimate the amount of sediment transport in Sombe River. In this research, direct measurements were carried out by taking sediment samples from the Sombe River, furthermore it is also used secondary data such as rainfall data and data characteristics of the watershed. The results of the analysis using the Yang method show that the average value of sediment transport in the Sombe River with a return period of 1 year, 2 years, 5 years and 10 years is 5.7x106 - 7.5x106 tons / year.